2022
DOI: 10.1038/s41598-022-12657-9
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole/reduced graphene oxide composites coated zinc anode with dendrite suppression feature for boosting performances of zinc ion battery

Abstract: Metallic zinc (Zn) anode has been received a great promise for aqueous rechargeable zinc-ion batteries (ZIBs) due to its intrinsic safety, low cost, and high volumetric capacity. However, the dendrite formation regarding the surface corrosion is the critical problems to achieve the high performance and the long lifespans of ZIBs. Here, we purpose the facile cyclic voltammetry deposition of polypyrrole/reduced graphene oxide (PPy/rGO) composites coated onto Zn 3D surface as Zn anode for ZIBs. As results, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…(3) sub + Q e = Zn tried to form composite with 2D nanosheets, achieving an improved ZIB performance [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97].…”
Section: D Materials For Advanced Zn Metal Anodesmentioning
confidence: 99%
“…(3) sub + Q e = Zn tried to form composite with 2D nanosheets, achieving an improved ZIB performance [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97].…”
Section: D Materials For Advanced Zn Metal Anodesmentioning
confidence: 99%
“…Another study found that the Zn‐PPy/rGO//MnO 2 battery could produce an excellent initial discharge capacity of 325 mAh g −1 at 0.5A/g, while maintaining up to 50% of its capacity after 300 cycles. These studies show the potentials of using composites, made of graphene and polypyrrole as electrode materials for Zn‐ion batteries and hybrid supercapacitors, underscoring the need for continuous and dedicated study to fully explore their applications in energy storage 23 …”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a single layer of carbon atoms that has distinct electronic and mechanical characteristics, 20 while polypyrrole is a conducting polymer with excellent electrochemical properties 21 . Zn‐ion batteries are becoming increasingly attractive for energy storage in various industries, including renewable energy and electric cars; thanks to these materials' promised improvements in the stability and capacity of the resulting devices made of these materials 22,23 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the organic electrolytes used in LIBs are generally toxic and flammable, which likely cause huge safety issues [6–9] . Therefore, development of non‐lithium battery technology with high safety and cost effectiveness is highly desirable [10,11] . In this regard, zinc‐ion batteries (ZIBs) that use nonflammable aqueous electrolytes represent a promising candidate capable of enabling intrinsic safety [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Therefore, development of non-lithium battery technology with high safety and cost effectiveness is highly desirable. [10,11] In this regard, zinc-ion batteries (ZIBs) that use nonflammable aqueous electrolytes represent a promising candidate capable of enabling intrinsic safety. [12,13] Moreover, the abundant natural resources and cost effectiveness of Zn exhibit great potential in large-scale energy storage.…”
Section: Introductionmentioning
confidence: 99%